IMPORTANCE OF INTERPROFESSIONAL EDUCATION, PRACTICE AND RESEARCH IN THE PHARMACY CURRICULUM IN THE ERA OF GLOBALIZATION - Dash, Alekha K.; Monaghan, Michael S. (European Scientific Journal, ESJ, 2015)
The profession of pharmacy has evolved gradually for more than a century and has seen many educational challenges and reforms. The pharmacy curriculum is science-based and varies widely in different parts of the world in both content and outcomes. The global pharmacy curriculum could be broadly categorized as product/industry-focused or patient-focused. In the United States (US), the baccalaureate degree has been replaced with the entry level Doctor of Pharmacy (Pharm.D.) curriculum. This change was designed to enable practicing pharmacists to provide patient care services that optimize medication therapy outcomes and promote health, wellness and disease prevention. This shift from a product-centered to a patient-centered curriculum has offered tremendous benefits to patients, society and healthcare. It has further been realized that working as a collaborative team with an inter-professional approach produces effective patient-centered outcomes. Implementation of inter-professional education (IPE), practice and research was recognized by pharmacy educators and accreditation authorities in the US in the early part of 21st century. IPE is now considered a standard for pharmacy accreditation. This review will compare some of the pharmacy curriculums of the world and the difficulty in harmonization of pharmacy curricula. The factors that facilitate and hinder IPE, practice and research in the curriculum will be discussed.